Indeks harga saham gabungan (ihsg) dan jakarta interbank offered rate (jibor); kinerja reksadana campuran - Tricahyadinata, Irsan (INOVASI, 2016)
The purpose of this study was to determine the effect of Composite Stock Price Index and Jakarta Interbank Offered Rate on the Performance Mixed Mutual Fund. Samples in this study was taken from firms that sell mutual funds in Indonesia, one of the companies that make the sample in this study is PT. Manulife Asset Management Indonesia, namely mutual funds mix traded and listed on the Stock Exchange the period January 2, 2015 until December 30, 2015 totaling 254 samples of daily data. The results showed that IHSG positive and significant effect on the performance of mutual funds. It shows that the higher the IHSG it will be the performance of mixed funds and conversely the lower the stock index will be more influenced not good on the performance of diminishing because of the composition of mixed funds largely in the form of shares IHSG is an indicator of the value of shares. JIBOR positive and significant effect on the performance of mutual funds. It shows that the greater the JIBOR it will affect both the Nab Mixed mutual fund, and vice versa JIBOR The lower the interest rate it will not affect either the performance of the mixed funds Nab. In this case the interest rate JIBOR can become a reference in the decision to invest in mixed funds because it has significant influence when JIBOR rise will affect the performance Nab mutual funds increased and if the fall will affect the performance Nab decreased hopefully this research can be a consideration in taking investment decision.Keyword: Composite Stock Price Index, Jakarta Interbank Offered Rate, Performance Mixed Mutual Fund.